Quantification of Pesticide Residues in Selected Vegetables using the QuEChERS Method - Meragal Kulathilakage Lasanthi Kumari Rajapakse; Nimsha Sevwandika Weerakkody; Pulippu Widana Yoshida Lakshani (The Open University of Sri Lanka, 2018)
Pesticide residues in fruits and vegetables have become a major problem in Sri Lanka. Therefore, there is a need to optimize the Quick, Easy, Cheap, Effective, Rugged and Safe (QuEChERS) method to determine pesticide residues in fruits and vegetables and assure the safety of food. The objectives of this study were to optimize the method for multi-residue pesticide analysis, to develop calibration curve to detect concentration of pesticides and to determine prevalence of five pesticide residues in locally grown vegetables tomato, cabbage and capsicum in Puttalum, Dambulla and Nuwara Eliya districts. Pesticide residues were determined by Gas Chromatography with Mass Spectrometry after multi residue extraction procedure (QuEChERS method). The QuEChERS method was validated using five pesticides named Diazinon, Chlopyrifos, Fipronil, Prothiofos and Tebuconazole and their retention times in minutes were15.948, 19.566, 20.342, 22.308, and 26.201 respectively. Coefficient of detection was obtained near 0.99 for all tested standard pesticides confirming the accuracy of the test method. Out of 45 vegetables samples, 15 samples were detected withpesticide residues, either Chlopyrifos, Prothiofos or Tebuconazole. However, pesticide residual values were less than Maximum Residual Levels for all the tested pesticides. Tebuconazole was the mostly detected pesticide residue with 0.128 ppm and 0.052 ppm in tomato and cabbage collected from Matale and Puttlum districts respectively. Therefore, it is important to collect samples while obtaining farmer details including the type of pesticide applied, harvesting interval and frequency and application rate of pesticide for further study.